A participação popular como ideário de concreção do controle social: uma análise do trabalho do Conselho Municipal de Assistência Social de Maracanaú - Matos, Maria do Socorro Lima Martins (2014)
With regard to public policy, the 1988 Federal Constitution has prescribed the political and administrative decentralization and a new look towards the way to think them, to set them and put them into execution. It was introduced in its grammar the idea of social control to be consolidated with the creation of spaces for discussion and deliberation as to its content, its recipients, its forms, its size and scope. The popular participation was thus assured. The councils in the different spheres of government (federal, state, county and municipal), were instituted as this ideal opportunity for participation and the concretion of the social control. The relevance of this study brand yourself because of being focused on the assessment of how and to what extent the social control of the actions listed in the sphere of social assistance policy in the town of Maracanaú is done through popular participation, understood here as the effective role of civil society in three ways established: social assistance entities, users and workers welfare. It is a qualitative research. For the purpose of this academic enterprise, the case study as a social research method, proved to be promising, as it offers rich possibilities of understanding the intricacies of popular participation in primary instance of the social control - advice – of the social welfare policy. This study presents an outline of how the Municipal Council of Social Assistance of Maracanaú is designed to popular participation in the public policy of social assistance and how this affects the participation in the exercise of social control, a key element for the success - or failure - of any public policy. In this report we present the theoretical bases of support and the categories that guided this research. To operationalize of the analysis and evaluation of the policy was used specific documentation of the Municipal Council of Social Assistance of Maracanaú for the years 2011 and 2012 as well as interviews with board members, executive secretary and manager of municipal policy of social assistance. In concluding, the study points out a transformation process occurring in that council, which affects the way the social control has been exercised in Maracanaú.